Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00270-013-0705-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Visceral Aneurysm Using Multilayer Stent: Two-Year Follow-Up Results in Five Consecutive Patients

Abstract: Long-term results in a wider population are needed to validate the effectiveness of the CMFM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 15 publications
0
27
0
2
Order By: Relevance
“…Development of flow-diversion devices for treatment of aneurysm created a paradigm shift from traditional stent-grafts. Flow diversion concept of excluding aneurysm with a passive physical barrier has been successful in managing peripheral and visceral aneurysms (10)(11)(12)(13). Recently, the use of flow diversion stent device has been extended to treat complex aortic aneurysm with encouraging medium-term clinical outcomes (14-16).…”
Section: Introductionmentioning
confidence: 99%
“…Development of flow-diversion devices for treatment of aneurysm created a paradigm shift from traditional stent-grafts. Flow diversion concept of excluding aneurysm with a passive physical barrier has been successful in managing peripheral and visceral aneurysms (10)(11)(12)(13). Recently, the use of flow diversion stent device has been extended to treat complex aortic aneurysm with encouraging medium-term clinical outcomes (14-16).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the continuity equation and Navier–Stokes equation are shown as follow.where P and u are pressure and blood velocity, respectively. In the computational models, the density (ρ) and dynamic viscosity (μ) were set as 1055 kg/m 3 and 3.5 × 10 −3  kg/ms [11], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Lowe et al [9] reported 14 patients were treated with MS, 7 patients died including one fatal rupture; Vojko et al [10] reported a 50-year-old man with two juxtarenal saccular aneurysms of abdominal aorta was treated with MS, and it showed the continuous shrinkage of the aneurysm sac in a 1 year follow-up. Alberto et al [11]. implanted 5 MSs in 5 patients to treat hepatic artery aneurysms, 2 years follow-up showed technical successes; Morris et al [12] treated visceral artery aneurysms (VAAs) in 5 patients with MSs and technical successes were achieved for all patients; Bouillot et al [13] compared the process of intracranial aneurysms (IAs) treated with flow diverter stents through both PIV and CFD, the results showed there was a good PIV–CFD agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical results have been published on the MFM device used to treat aortic, peripheral and visceral aneurysms [7][8][9][15][16][17]. However, there is paucity of long-term data in relation to this new device, with current literature reporting relatively short follow up results [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is paucity of long-term data in relation to this new device, with current literature reporting relatively short follow up results [15][16][17]. When conducted strictly in accordance with the device instructions for use (IFU), deployment of the MFM has produced consistently positive outcomes in aortic pathologies including TAAA and aortic type B dissections [7][8][9]15].…”
Section: Discussionmentioning
confidence: 99%